Syntheses of Some 3,5-Diaryl-4H-1,2,4-triazole Derivatives and their Antifungal Activity - Ram Janam Singh; Dharmendra Kumar Singh (E-Journal of Chemistry)
Syntheses of a series of 3, 5-diaryl-4H-1, 2, 4-triazole derivatives are described. In this present work, 4-amino-3-phenyl-5-p-tolyl-4H-1,2,4-triazole(1) was converted to N,N’-bis[3-phenyl-5-p-tolyl-4H-1,2,4-triazolyl]-1,4-xylenediimine(2) and 3-Phenyl-5-p-tolyl-4-[4-methyl benzylidenamino]-4H-1,2,4-triazole (3) in good yields by treatment with aldehydes OHC-C6H4-CHO and Ar-CHO respectively. The compounds N,N’-bis [3-phenyl-5-p-tolyl-4H-1,2,4-triazolyl]-1,4-xylenediimine (2) and 3-phenyl-5-p-tolyl-4-[4-methyl benzylidenamino]-4H-1,2,4-triazole (3) were reduced with NaBH4 to afford the corresponding compounds N,N’-bis [3-phenyl-5--tolyl-4H-1,2,4-triazolyl]-1,4-xylenediamine (4) and 3-phenyl-5-p-tolyl-4-[4-methyl benzylamino]-4H-1,2,4-triazole (5) respectively. The newly synthesized compounds were characterized by spectral and elemental analyses. All the synthesized compounds were tested for their antifungal activity against P.oryzae, B. cinerea, A. niger, C. albicans and T. rubrum.